Talking to the audience : Shakespeare, performance, self - Escolme, Bridget, 1964- (Routledge, 2005)
This unique study investigates the ways in which the staging convention of direct address - talking to the audience - can construct dramatic subjectivity, or selfhood, in Shakespeare plays.